Fulfilling the Rights of Restitution for Victims of Fraudulent Investment Fraud - Nur Azisa; Syarif Saddam Rivanie Parawansa; Ulil Amri; Devian Yulansari Darwis (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The fraudulent investment mode of fraud is carried out by the perpetrators with a fake fund collection program with the lure of large percentage returns and low risk, and does not require technical analysis to make a profit. For victims of fraudulent investment fraud, paying attention to the provision of restitution as a form of legal protection. In practice, law enforcers still pay little attention to efforts to fulfill restitution for victims who have suffered losses. The type of research used is normative research using a statutory approach and a case approach. As for now, arrangements regarding restitution in criminal acts have been regulated in several laws, but in practice, several factors influence them, including statutory regulations, judges' legal understanding factors, and victims' legal understanding factors, so that their implementation still relies on victims' initiatives to apply for restitution